The roots of William Tyndale's theology - Werrell, Ralph S. (James Clarke & Co, 2013)
"In this follow-up to his previous work, The Theology of William Tyndale, Ralph Werrell draws on his close acquaintanceship with Tyndale's writings to develop a new understanding of the foundations of the great English Reformer's theology. The common assumption that the Reformation started with Luther has, in the author's opinion, harmed research into the English Reformation and a consideration of the Reformation theology of William Tyndale in particular. The author asserts that Tyndale was not influenced by the Continental Reformers to the substantial extent that academics have claimed, and that his theology was fully developed by the time he wrote the 'Preface' and marginal notes for his 1525 translation of the New Testament. The author considers the possible influences of many theologians on Tyndale's theology to reveal the primary importance of the thought of the Wycliffites and John Trevisa. The influence of the Church Fathers, Luther, Erasmus, and other humanists is also considered. The second half of the book outlines the various areas of Tyndale's theology (the place of the sacraments, the doctrine of the Trinity, the church and state) and emphasises the paramount importance of his 'blood of Christ' doctrine and its effective role in creation, the Fall, and man's salvation."--Publisher.
Print version record.
Includes bibliographical references (pages 180-188) and index.
Master record variable field(s) change: 050, 072
Keywords: Tyndale, William, -- -1536 -- Religion; Tyndale, William, -- -1536; Theology; Theology -- History -- 16th century; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Religion; Theology; RELIGION / Christian Theology / General; 1500-1599; Electronic books; History